Ambivalent improvements: biography, biopolitics, and colonial Delhi - Stephen, Legg (Pion, 2008)
This paper explores the ambivalent feelings towards the Government of India produced in one of the government’s own employees. In establishing the Delhi Improvement Trust in the 1930s, Arthur Parke Hume had to battle against governmental cost cutting in an attempt to secure the rehousing of slum evictees. The refusal of the government to accept this welfarist commitment to investment led to the stalling of the improvement projects and great emotional disquiet for Hume. This is traced through his personal correspondence with his parents. In interweaving these insights with the imperial archive, three biographical approaches are adopted. A traditional chronology is used to order the events, an analytical approach is used to outline the discursive regularities of Hume’s observations, and a genealogical approach is used to suggest the influences on Hume’s writings and the broader governmental rationalities that he had to negotiate.